CPT2 downregulation adapts HCC to lipid-rich environment and promotes carcinogenesis via acylcarnitine accumulation in obesity. Issue 8 (6th February 2018) - Fujiwara, Naoto; Nakagawa, Hayato; Enooku, Kenichiro; Kudo, Yotaro; Hayata, Yuki; Nakatsuka, Takuma; Tanaka, Yasuo; Tateishi, Ryosuke; Hikiba, Yohko; Misumi, Kento; Tanaka, Mariko; Hayashi, Akimasa; et al.
Abstract : Objective: Metabolic reprogramming of tumour cells that allows for adaptation to their local environment is a hallmark of cancer. Interestingly, obesity-driven and non-alcoholic steatohepatitis (NASH)-driven hepatocellular carcinoma (HCC) mouse models commonly exhibit strong steatosis in tumour cells as seen in human steatohepatitic HCC (SH-HCC), which may reflect a characteristic metabolic alteration. Design: Non-tumour and HCC tissues obtained from diethylnitrosamine-injected mice fed either a normal or a high-fat diet (HFD) were subjected to comprehensive metabolome analysis, and the significance of obesity-mediated metabolic alteration in hepatocarcinogenesis was evaluated. Results: The extensive accumulation of acylcarnitine species was seen in HCC tissues and in the serum of HFD-fed mice. A similar increase was found in the serum of patients with NASH-HCC. The accumulation of acylcarnitine could be attributed to the downregulation of carnitine palmitoyltransferase 2 (CPT2), which was also seen in human SH-HCC. CPT2 downregulation induced the suppression of fatty acid β-oxidation, which would account for the steatotic changes in HCC. CPT2 knockdown in HCC cells resulted in their resistance to lipotoxicity by inhibiting the Src-mediated JNK activation. Additionally, oleoylcarnitine enhanced sphere formation by HCC cells via STAT3 activation, suggesting that acylcarnitine accumulation was a surrogate marker of CPT2 downregulation and directly contributed to hepatocarcinogenesis. HFD feeding and carnitine supplementation synergistically enhanced HCC development accompanied by acylcarnitine accumulation in vivo. Conclusion: In obesity-driven and NASH-driven HCC, metabolic reprogramming mediated by the downregulation of CPT2 enables HCC cells to escape lipotoxicity and promotes hepatocarcinogenesis.